Perancangan Multi Node Web Server Menggunakan Docker Swarm dengan Metode Highavability - Ahmad Rivaldi; Ucuk Darusalam; Deny Hidayatullah (STMIK Budi Darma, 2020)
Container-based virtualization is very popular among programming development in a lightweight virtualization because where the Linux kernel can divide resource-using containers to prevent uninterrupted performance between And as a burden divider in tackling the many incoming bandwidth. One of the most commonly used container-based virtualization is Docker. Docker itself is an open source software that can be changed to your liking. Docker containers can be used for clustering Web servers. It aims to reduce